The Influence of Fibrinogen and Fibrin on Thrombin Generation - Evidence for Feedback Activation of the Clotting System by Clot Bound Thrombin - Kumar, Rachana; Béguin, Suzette; Hemker, H Coenraad (Thrombosis and Haemostasis, 1994)
In plasma the bulk of thrombin generation takes place after a clot has formed. We therefore investigated in what way the clot influences thrombin generation in plasma. The forming clot withdraws thrombin from free solution. Consequently less thrombin activity is found and less thrombin-inhibitor complexes are formed. The thrombin that is adsorbed to the clot reduces the lag time before thrombin generation in intrinsically or extrinsically triggered platelet poor plasma as well as in platelet rich plasma. We investigated the mechanism of this activation.Clots were obtained by recalcification of plasma or by the addition of thrombin-like enzymes (Reptilase, Agihal) from snake venoms. They were thoroughly washed until the washing fluid was devoid of any detectable clotting enzyme activity. In platelet poor plasma (PPP), thrombin-induced clots shorten the factor Va-dependent lag-time of thrombin generation in the extrinsic system as well as the factor VUIa-dependent thrombin generation in the intrinsic system. Factor V or factor VII preparations that in itself hardly influence thrombin generation patterns aquire the capacity to shorten these lag-times when incubated with clot. The last washing fluid of the clot is inactive. Snake venom induced clots are not active either. Clots that are incubated in heparinised plasma for 1 h or more are as active as clots from normal plasma are. A role of factor Xa can not be excluded but must be minor because a clot made by addition of thrombin to plasma from which the factors II, VII, IX and X have been removed is as active as a clot from normal plasma is.When added to recalcified platelet rich plasma (PRP), in which the lag-time of thrombin formation is dependent upon activation of platelet procoagulant phospholipid activity, any type of clot shortens the lagtime before the burst of thrombin generation. Clots that are obtained by snake venom enzymes are also active in this system. This indicates that fibrin alone is capable to induce the procoagulant phospholipid activity in platelets.We conclude that three known thrombin-dependent feedback activations in the clotting system (factor V, factor VIII and platelets) are efficiently supported by thrombin bound to the fibrin clot and that there is an additional activating effect of fibrin on the procoagulant action of platelets.